Content of matrix metalloproteinases in the blood of hypertensive patients with a high cardiovascular risk receiving statin therapy - V. P. Mikhin; O. A. Osipova; V. V. Vorotyntseva; D. N. Perutsky; N. I. Golovina (Кардиоваскулярная терапия и профилактика, 2022)
Aim. To compare the effect of atorvastatin and rosuvastatin as part of complex therapy in patients with hypertension (HTN) with a high cardiovascular risk on the level of matrix metalloproteinases -1, -9 (MMP-1, MMP-9) and tissue inhibitors of metalloproteinases -1, -4 (TIMP-1, TIMP-4).Material and methods. The study included 140 hypertensive patients who received atorvastatin (Liprimar) 20 mg/day in addition to antihypertensive therapy for a year, which was later replaced by rosuvastatin (Rosucard) in the following doses: 10 mg/day (n=96), 20 mg/day (n=24), 40 mg/day (n=26). Patients underwent standard clinical and paraclinical investigations. In the blood serum of patients, the levels of MMP-1, MMP-9 and TIMP-1, TIMP-4 were determined.Results. Patients who used rosuvastatin at a dose of 40 mg/day had a more pronounced decrease in MMP-1 than those treated with rosuvastatin at a dose of 10 and 20 mg/day (p<0,05), while there were no differences in MMP-1 when using low and medium doses. Rosuvastatin had a less pronounced effect on MMP-9 than on MMP-1, while increasing the dose of rosuvastatin did not affect the intensity of MMP-9 reduction (p>0,05). The content of TIMP-1 and TIMP-4 increased when taking rosuvastatin, while a more pronounced dose-dependent increase in TIMP-1 was observed with rosuvastatin 20 mg/day and 40 mg/day. In addition, the largest increase in TIMP-4 was observed when using rosuvastatin at a dose of 40 mg/day. Atorvastatin had no significant effect on MMP-1 and MMP-9, as well as TIMP-1 and TIMP-4.Conclusion. Long-term rosuvastatin therapy (10 mg/day, 20 mg/day, 40 mg/day) as part of the complex therapy of cardiovascular patients affects the metabolism of vascular wall elastin and collagen, reducing the level of MMP-1, MMP-9 and increasing the content of TIMP-1, TIMP-4 in the blood.